2002
DOI: 10.1007/s00424-002-0844-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP has distinct effects from Ca 2+ in evoking priming and fusion/exocytosis in parotid amylase secretion

Abstract: Rat parotid acinar cells were perfused in small quartz columns to examine the role of cAMP and Ca(2+) in the priming and fusion/exocytosis of amylase secretion. Carbachol (CCh) evoked a biphasic response of amylase secretion with an initial rapidly occurring large peak and a subsequent sustained plateau. Isoproterenol produced slowly increasing amylase secretion that reached the plateau greater than that induced by CCh. Combined stimulation with isoproterenol and CCh greatly potentiated amylase secretion. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Occasionally, one or two stepwise events were seen superimposed on the smooth change in C m . The absence of C m steps was surprising because 1 M Iso has been shown to efficiently induce amylase release from parotid acini (34) and may indicate that adrenergic signaling is compromised in single cells or that another vesicle population whose fusions cannot be resolved as individual events can be induced by lower concentrations of agonist to release amylase.…”
Section: Exocytosis Induced By Camp and Camentioning
confidence: 99%
See 1 more Smart Citation
“…Occasionally, one or two stepwise events were seen superimposed on the smooth change in C m . The absence of C m steps was surprising because 1 M Iso has been shown to efficiently induce amylase release from parotid acini (34) and may indicate that adrenergic signaling is compromised in single cells or that another vesicle population whose fusions cannot be resolved as individual events can be induced by lower concentrations of agonist to release amylase.…”
Section: Exocytosis Induced By Camp and Camentioning
confidence: 99%
“…For example, in parotid and pancreatic acinar cells, fluid and protein secretion is regulated by both parasympathetic and sympathetic input. In the parotid, cholinergic or ␤-adrenergic receptor activation evokes rises in cytosolic Ca 2ϩ concentration ([Ca 2ϩ ] i ) and CAMP concentration, respectively, and both messengers can act as intracellular messengers to induce amylase release (34). A primary difference between parotid and pancreatic acinar cells is that robust exocytosis in the parotid can be stimulated by increased cytosolic levels of cAMP.…”
mentioning
confidence: 99%
“…Recently, Yoshimura et al (45) suggested that cAMP sensitizes induced amylase secretion by priming zymogen granule Fig. 8.…”
Section: ϫ12mentioning
confidence: 99%
“…Colchicine may affect some intracellular signaling sites between receptors and Cl − channels, in turn modulating protein secretion, channel activity, and receptor function (4,12,19,24 (4,5,24,37). The interaction between Ca 2+ and cAMP signaling systems enhances amylase secretion (21,39), but this enhancement does not require cortical actin integrity. Exocytosis of amylase consists of three types of processes: constitutive-like exocytosis, minor regulated exocytosis, and major regulated exocytosis (6).…”
Section: Discussionmentioning
confidence: 99%
“…This interaction modulates both signaling systems (28), which exert different actions on amylase secretion (6,23,39) and translocation of Rap1 (8), but a similar action on cofilin dephosphorylation (35). Some of these processes might be sensitive to changes in the cytoskeletal integration.…”
Section: References Interaction Of Camentioning
confidence: 99%